KERAGAMAN JENIS LALAT DAN EKTOPARASIT (JAMUR) PADA KAKI LALAT DI PASAR PETERONGAN KOTA SEMARANG - Fadhila, Aulia Nur; Sutiningsih, Dwi; Martini, Martini (Jurnal Kesehatan Masyarakat (Undip), 2022)
Flies are one of a mechanical vector that could spread a lot of disease, they also often get associated as a carriers of diseases such as cholera, typhoid, dysentery, diarrhea, and etc. The presence of flies itself in one place can be used as an indicator that the area was less hygienic. The purpose of this research was to find out the diversity of fungi and flies at the Peterongan Market, Semarang. This research was an explanatory study that was using a survey method and laboratory examination with cross sectional approach. The population of this study was all the flies that caught at the Peterongan Market, Semarang. The sampling was done by using accidental sampling at three different stalls on the ground floor of Peterongan Market. There was 25 flies that caught in this research, including of Musca domestica, Phaenicia sericata, and Sarcophaga. There was also several fungal spores that accidently carried by the flies on their feet just like Mucor, Rhizopus arrhizus (Rhizopus oryzae), Aspergillus fumigatus, Aspergillus flavus. Most common flies and fungal spores that found in this research was Musca domestica and Aspergillus.